The Impact of The Environmental Temperature-Humidity Index on Ammonia Concentration (NH3) in Laying Hen Farming - Sara, Urfiana; Azhar, Muhammad; Yunus, Muhammad; Rasuli, Nur; Fastawa, Rajma (State Islamic University of Sultan Syarif Kasim Riau, 2025)
Emissions of ammonia gas (NH3) produced from the manure of laying hens can harm health and productivity. This study aims to determine the comfort level of laying hens based on the temperature humidity index which is calculated based on the temperature and humidity conditions of the cage, and its relationship with ammonia gas (NH3) levels, as well as the factors that most influence the concentration of ammonia gas (NH3) around the cage. Data collection was carried out in 96 units of laying hen cages in Sidrap Regency spread across 4 sub-districts, including; Kulo, Pitu Riawa, Maritengngae, and Watang Pulu. Data collection was carried out directly by measuring the ammonia levels in the cage air using the Ammonia Gas Detector Smart Sensor AR8500 system. Temperature and humidity were measured using an Elitech DT-3 Thermo Hygrometer. Data were analyzed by correlation and multiple linear regression. The results of the research showed that as many as 53.13% of laying hens were in an